CaFeAl mixed oxide derived heterogeneous catalysts for transesterification of soybean oil to biodiesel. (August 2015) - Lu, Yongsheng; Zhang, Zaiwu; Xu, Yunfeng; Liu, Qiang; Qian, Guangren
Highlights: CaFeAl/LDO was firstly used as a novel catalyst for transesterification reaction. CaFeAl/LDO catalyst exhibited a prominent catalytic activity and stability. The optimal catalytic reaction conditions were found. CaFeAl/LDO had the strong ability of reusability and able to use more than 8 runs. Abstract: CaAl layered double oxides (LDO) were prepared by co-precipitation and calcined at 750 °C, and then applied to biodiesel production by transesterification reaction between methanol and soybean oil. Compared with characteristics of CaFe/LDO and CaAl/LDO, CaFeAl/LDO had the best performance based on prominent catalytic activity and stability, and achieved over 90% biodiesel yield, which stayed stable (over 85%) even after 8 cycles of reaction. The optimal catalytic reaction condition was 12:1 M-ratio of methanol/oil, reaction temperatures of 60 °C, 270 rpm stirring rate, 60 min reaction time, and 6% weight-ratio of catalyst/oil. In addition, the CaFeAl/LDO catalyst is insoluble in both methanol and methyl esters and can be easily separated for further reaction, turning it into an excellent alternative for biodiesel synthesis.